Advanced‐stage mycosis fungoides: role of the signal transducer and activator of transcription 3, nuclear factor‐κB and nuclear factor of activated T cells pathways. (25th July 2019) - Pérez, C.; Mondéjar, R.; García‐Díaz, N.; Cereceda, L.; León, A.; Montes, S.; Durán Vian, C.; Pérez Paredes, M.G.; González‐Morán, A.; Alegre de Miguel, V.; Sanz Anquela, J.M.; Frias, J.; et al.
Summary: Background: The malignant mechanisms that control the development of cutaneous T‐cell lymphoma (CTCL) are beginning to be identified. Recent evidence suggests that disturbances in specific intracellular signalling pathways, such as RAS–mitogen‐activated protein kinase, T‐cell receptor (TCR)–phospholipase C gamma 1 (PLCG1)–nuclear factor of activated T cells (NFAT) and Janus kinase (JAK)–signal transducer and activator of transcription (STAT), may play an essential role in the pathogenesis of CTCL. Objectives: To investigate the mechanisms controlling disease development and progression in mycosis fungoides (MF), the most common form of CTCL. Methods: We collected 100 samples that were submitted for diagnosis of, or a second opinion regarding, MF between 2001 and 2018, 80% of which were in the early clinical stages of the disease. Formalin‐fixed paraffin‐embedded tissues were used for histological review and to measure the expression by immunohistochemistry of surrogate markers of activation of the TCR–PLCG1–NFAT, JAK–STAT and NF‐κB pathways. Folliculotropism and large‐cell transformation were also examined. Results: NFAT and nuclear factor kappa B (NF‐κB) markers showed a comparable activation status in early and advanced stages, while STAT3 activation was more frequent in advanced stages and was associated with large‐cell transformation. Consistently with this observation, STAT3 activation occurred in parallel with MF progression in two initially MF‐negative cases. A significant association of NFAT with NF‐κB markers was also found, reflecting a common mechanism of activation in the two pathways. Genomic studies identified nine mutations in seven genes known to play a potential role in tumorigenesis in T‐cell leukaemia/lymphoma, including PLCG1, JAK3 and STAT3, which underlies the activation of these key cell‐survival pathways. A higher mutational allele frequency was detected in advanced stages. Conclusions: Our results show that STAT3 is activated in advanced cases and is associated with large‐cell transformation, while the activation of NFAT and NF‐κB is maintained throughout the disease. These findings could have important diagnostic and therapeutic implications. What's already known about this topic? Mycosis fungoides is characterized by a clonal expansion of T cells in the skin. The mechanisms controlling disease development and progression are not fully understood. What does this study add? An association of the nuclear factor of activated T cells and nuclear factor kappa B pathways was found, which could reflect a common mechanism of activation. These pathways were activated in early and advanced stages at the same level. Signal transducer and activator of transcription 3 activation was associated with large‐cell transformation and was more frequent in advanced stages. A genomic analysis of cutaneous T‐cell lymphoma‐associated genes was performed. Nine mutations were detected. What is the translational message? These results could have important implications for the treatment of MF in the near future. Abstract : Linked Comment: Ødum. Br J Dermatol 2020; 182 :16–17 .